Kyai, Secret Married and Social Legitimacy: Marriage Practices in Rembang, Pasuruan, East Java - Muzakki, M. Harir; Khaidarulloh, Khaidarulloh; Hasan Wahid, Soleh (Fakultas Dakwah Institut Agama Islam Sunan Giri Ponorogo, 2025)
This article examines the practice of secret marriage in Pekoren Village, Rembang District, Pasuruan Regency, East Java, with a focus on the central role of the kyai (Islamic cleric) in legitimizing the practice. Using a qualitative approach and ethnographic methods, this study explores how local religious authority constructs, negotiates, and sustains social legitimacy for marriages that are not legally recognized by the state. The study finds that the authority of the kyai is neither singular nor absolute, but shaped through complex social, symbolic, and economic relationships. Secret marriage occurs in various contexts, including late-life marriages, suspended marriages due to age restrictions, and polygamous marriages without official permission. The kyai serves as a mediator between religious norms and state legal pressures, offering religious legitimacy when the formal legal system is perceived as inadequate. This article shows that state law and local norms intersect through a space of compromise maintained by cultural-religious authority. Drawing on Khaled Abou El Fadl’s theory of authority and Max Weber’s theory of social action, the article underscores the importance of understanding legal pluralism and social authority in grassroots family law practices in Indonesia.